Use of whole-slurry from autohydrolyzed Eucalyptus wood for bioethanol production - Romaní, Aloia (2014)
The development of a cost-effective process on large-scale is one of the most important targets in the second generation bioethanol. The use of pretreated whole-slurry allows savings in washing-steps and water consumption. In this work the whole-slurry from pretreated Eucalyptus wood (EW) was used for the bioethanol production by saccharification and fermentation process. Firstly, EW was submitted to autohydrolysis treatment and the slurry obtained was employed for the optimization of enzymatic saccharification using an experimental design. The optimized conditions were employed for bioethanol production using a robust industrial Saccharomyces cerevisiae strain. The highest ethanol concentration obtained was 50 g/L corresponding to an ethanol conversion of 95 %.